SISTEM PENGELOLAAN DATA BERBASIS WEB DAN PELATIHAN BAGI PENGURUS TPQ AL-MUBAAROK SURABAYA - rausanfita, alqis; Vessa Rizky Oktavia; Ahmad Wali Satria Bahari Johan; Moch. Andi Divangga Pratama; Fendi Virgiansyah; Muhammad Hanafi Choirulloh (Politeknik Negeri Sriwijaya, 2024)
TPQ Al-Mubaarok, an institution for Quranic learning located in Surabaya, is currently facing challenges in managing student data. Presently, information regarding the students is manually recorded in logbooks, posing a hindrance for the administrators of TPQ Al-Mubaarok to efficiently manage and analyze data. In order to address this issue, we aim to develop a web-based system that facilitates the digital recapitulation process of data. This endeavor begins with conducting field surveys to understand user needs. Subsequently, we proceed to the system design phase and interface design to cater to these needs. System implementation follows the design phase, where we integrate all planned features into a functional system. Next, we conduct system trials involving the authors and the main users of the system, the ustadz/ustadzah. These trials are conducted to ensure that the system operates smoothly and meets user requirements. Finally, we evaluate user satisfaction with the system, particularly from the perspective of the ustadz/ustadzah. The implementation of this system is expected to provide significant benefits, including expediting the registration process for new students, facilitating access to information regarding donations, and providing facilities for managing and summarizing student data more efficiently